Review Article on the All-On-Four Treatment Concept in Dental Implants - Soyfer, Vladimir (Archives of Surgery and Clinical Research, 2023)
Edentulism, a condition characterized by the absence of teeth, significantly impacts facial aesthetics, eating efficiency, and speech fluency, thereby diminishing the quality of life. This paper aims to explore the All-On-Four Treatment Concept in Dental Implants, a promising solution to this issue. The All-On-Four approach, though complex, offers a pathway to restore smile and functionality by using four strategically positioned implants to hold a temporary prosthesis. This prosthesis is later replaced by a permanent version after approximately four months. This swift oral restoration technique significantly enhances a patient’s self-confidence and overall life quality. The significance of this treatment lies in its potential to provide a less invasive and more affordable solution for severe jawbone atrophy, where the proximity of critical anatomical structures and compromised bone conditions may hinder other prosthetic solutions. The paper concludes with a discussion on the potential of the All-On-Four treatment to revolutionize dental implant procedures, offering a beacon of hope for individuals suffering from edentulism.